PENDIDIKAN KEMANDIRIAN BERBASIS GENDER (Nilai Pendidikan Pesantren di Indonesia) - Aziza Meria (Universitas Islam Negeri Imam Bonjol Padang, 2012)
Independence is one of the goals of education. The value of independence should be inculcated for of human being for independence grow is the most appropriate educational institution. Boarding school separates male and female students, independence education is easy to do. Dynamics of more boarding school is not just a process of education and teaching cognitive, but the emphasis on individual learning and community life, the formation of character, personality, mental and social development in the community. Independent education based on genderis one of the values and behavior should be had male and female students, to mate the survival. Keywords : Independence education, gender and boardingCopyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i2.59